Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.2478/eko-2020-0009
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Slope Exposure on the Soil Aggregation and Structure, Water Stability of Aggregates, and Ecological Microstructure Formation of the Ravine Forest Soils in Pre-Dnipro Region (Ukraine)

Abstract: AbstractThe soil aggregation and structure, water stability of aggregates, and peculiarities of microstructure formation of the ravine forest soils in Dnipropetrovsk region on the example of the northern variant of the ravine forest “Kapitanivskiy” have been identified. The soil properties of southern and northern ravine exposures have been compared. The soil structure, aggregate composition, water stability of aggregates as well as soil-forming processes of the ravine ecosyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Until recently, researchers expressed doubts that in steppe conditions, fullfledged chernozem soils could form under natural forest vegetation (Travleev, 1996). The results of complex studies carried out by Belova & Travleev (1999), Yakovenko (2017), Bozhko & Bilova (2020), Ponomarenko et al (2022), Yakovenko et al (2024) confirm the fact of the formation of chernozem soils under natural forest vegetation in the steppe zone of Ukraine.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Until recently, researchers expressed doubts that in steppe conditions, fullfledged chernozem soils could form under natural forest vegetation (Travleev, 1996). The results of complex studies carried out by Belova & Travleev (1999), Yakovenko (2017), Bozhko & Bilova (2020), Ponomarenko et al (2022), Yakovenko et al (2024) confirm the fact of the formation of chernozem soils under natural forest vegetation in the steppe zone of Ukraine.…”
Section: Introductionmentioning
confidence: 62%
“…The main factor in the steppe that limits the growth and development of forest vegetation is the amount of moisture (Belova & Travleev, 1999). The best conditions, from this point of view, are river valleys, as well as the middle and lower parts of the slopes, which differ from each other depending on the exposure, with the most contrasting differences being characterized by the northern and southern exposures (Belova & Travleev, 1999;Bozhko & Bilova, 2020 ). Ding et al (2024) found that soils on the northern slope have better physical properties than those on the southern slope.…”
Section: Introductionmentioning
confidence: 94%
“…A detailed description of the physical, chemical and micromorphological properties of the Calcic Chernozem studied in the steppe zone of Ukraine was presented in our previous works (Bilova, Travleev, 1999;Bozhko, Bilova, 2020;Gorban, 2019;Gorban, Boloban, 2019;Gorban et al, 2020;Recio Espejo et al, 2020, etc. ).…”
Section: Site Characteristicsmentioning
confidence: 99%